2009
DOI: 10.1348/096317908x288838
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support, career satisfaction, and the retention of older workers

Abstract: Through two studies with diverse samples, we tested a conceptual model of the relationships between organizational and career factors and older workers' intention to remain with their organization. Perceived organizational support mediated the relationship between training and development practices, hierarchical, and job content plateauing and intention to remain. Career satisfaction mediated the relationship between perceived organizational support, job content plateauing, and intention to remain. We conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
256
3
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(288 citation statements)
references
References 38 publications
21
256
3
8
Order By: Relevance
“…The result regarding the effect of POS on CSAT lends support to other studies in the relevant literature (Karatepe, 2012;Armstrong-Stassen and Ursel, 2009;Erdogan et al, 2004). The availability of sufficient support provided by the organization suggests that the organization values employees' contributions and cares about their well-being.…”
Section: Resultssupporting
confidence: 87%
“…The result regarding the effect of POS on CSAT lends support to other studies in the relevant literature (Karatepe, 2012;Armstrong-Stassen and Ursel, 2009;Erdogan et al, 2004). The availability of sufficient support provided by the organization suggests that the organization values employees' contributions and cares about their well-being.…”
Section: Resultssupporting
confidence: 87%
“…Thus, the researchers considered work engagement as a relatively stable motivational and individual difference variable (Park & Gursoy, 2012). Older employees continue working if they are successfully convinced to remain with the organization (Armstrong-Stassen & Ursel, 2009). Meanwhile, early retirement is seen as the outcome of poor work engagement.…”
Section: Factors Determining Work Engagement Of Older Employeesmentioning
confidence: 99%
“…Indeed, research has shown that it has consequences on several beneficial organizational outcomes such as job performance, employee commitment, occupational retention as well as organizational retention (e.g., Igbaria, 1991;Pachulicz, Schmitt and Kuljanin, 2008;Yap et al, 2010). Interestingly, in the context of an aging workforce, subjective career success has also been shown to influence older workers' intention to remain with their organization (Armstrong-Stassen and Ursel, 2009). In addition, individuals themselves take advantage of a sense of career success, as it has been shown to have not only desirable consequences in terms of life satisfaction and well-being (Hall, 2002), but also to be related to goal achievement, such as hierarchical status (Abele and Spurk, 2009).…”
Section: Résumé De L'articlementioning
confidence: 99%